1973
DOI: 10.1002/chin.197319207
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTH. EINIGER ALPHA‐ALKOXYALKYLHYDROPEROXIDE

Abstract: Durch Ozonierung der Olefine (I) in entsprechenden Alkanolen (II) bei ‐70°C werden die Hydroperoxide (III) dargestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…using TPTD, but the extracted mass spectrum had no satisfactory match in the Wiley Mass Spectral Database. However, on the basis of the results of recent gas-phase studies on ethene, 42 and liquidphase studies on numerous other alkenes, [43][44][45][46] it is expected that the major product of ozonolysis of 1-tetradecene in the presence of excess 2-propanol will be R-isopropoxytridecyl hydroperoxide formed by the mechanism shown in Figure 6E. This compound would most likely have a lower vapor pressure than tridecanoic acid, conforming with the TPTD results.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…using TPTD, but the extracted mass spectrum had no satisfactory match in the Wiley Mass Spectral Database. However, on the basis of the results of recent gas-phase studies on ethene, 42 and liquidphase studies on numerous other alkenes, [43][44][45][46] it is expected that the major product of ozonolysis of 1-tetradecene in the presence of excess 2-propanol will be R-isopropoxytridecyl hydroperoxide formed by the mechanism shown in Figure 6E. This compound would most likely have a lower vapor pressure than tridecanoic acid, conforming with the TPTD results.…”
Section: Resultssupporting
confidence: 67%
“…To test this hypothesis, a solution of 1-tetradecene in 2-propanol was ozonated and the product solution was atomized and analyzed by TDPBMS. The liquid-phase reaction is known to produce R-alkoxyalkyl hydroperoxides in near-quantitative yield, [43][44][45][46] so the excellent agreement between the TPTD spectrum of chamber aerosol and the liquid-phase mass spectrum (Figure 5D) is strong evidence that compound B is R-isopropoxytridecyl hydroperoxide. It is worth noting that hydroperoxides such as this may not be amenable to GC analysis (we have observed that they dehydrate to the corresponding esters) and would therefore be overlooked using traditional GC/MS identification procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid‐phase ozonolysis of the alkenes in the presence of carboxylic acids and alcohols is known as a very efficient preparation method of the α‐acyloxy and α‐alkoxy hydroperoxides . For the cyclic alkenes, the resulting α‐acyloxyhydroperoxy aldehydes contain both hydroperoxy and aldehyde moieties; therefore, compounds shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gas- () and liquid-phase () reactions of alkenes with O 3 have been widely studied, and the general reaction mechanisms are reasonably well-established and apparently similar in the two phases. Of particular relevance to the work presented here are recent investigations of gas-phase ozonolysis of ethene ( ) and liquid-phase reactions of normal alkenes ( ) carried out in the presence of alcohols and carboxylic acids. Ozonolysis of 1-tetradecene [CH 3 (CH 2 ) 11 CHCH 2 ] in the presence of the alcohols and carboxylic acids used here apparently occurs by the following pathways: The initial step in the reaction involves addition of O 3 to the alkene double bond, resulting in the formation of a 1,2,3-trioxolane (primary ozonide).…”
Section: Resultsmentioning
confidence: 99%
“…Ozone from a Welsbach T-408 O 3 generator (∼2% O 3 /O 2 ) was then bubbled through the solutions at ∼0.15 L/min for 60 s, which was sufficiently long to ozonize nearly all the alkene, without adding excess O 3 . This method should produce α-alkoxyalkyl and α-acyloxyalkyl hydroperoxides in nearly quantitative yields ( ). All reacted solutions were atomized in a Collison atomizer using dry, clean air as the carrier gas.…”
Section: Methodsmentioning
confidence: 99%